Strata, Scarabs and Synchronisms: A Framework for Synchronizing Strata and Artifacts. Issue 1 (23rd January 2020) - Levy, Eythan; Piasetzky, Eli; Finkelstein, Israel
This paper presents a formal framework for synchronizing strata and datable artefacts in multi-layered sites. We first present a simple set of rules regarding the definition of safe termini post quem, taking into account cases of uncertain dating and/or uncertain stratigraphic attribution of the artifacts. We then propose a definition of chronologically optimal termini post quem, and a procedure to represent these optimal termini graphically by a step function in a two-dimensional graph. We also propose a definition of chronologically critical artifacts, as a minimal set of artifacts that determine all the optimal termini post quem of a stratigraphic sequence. Finally, we define a measure of the robustness of a terminus post quem, expressed in terms of the number of different artifacts supporting this terminus . We illustrate our approach through the case study of Egyptian scarabs from the site of Beth Shean (northern Israel), a well-known Bronze and Iron Age site that hosted an Egyptian garrison during the New Kingdom (ca. 1540–1070 B.C.E.). We also provide a software utility which assists users in applying our methodology.